Respostas
respondido por:
2
| -2x - 7 | = 3
Teremos duas equações e duas soluções
-2x - 7 = 3
-2x - 7 = 3
-2x = 10
x = -5
e
-2x - 7 = -3
-2x = 4
x = -2
Portanto x = -5 ou x = -2 é solução da equação modular.
Teremos duas equações e duas soluções
-2x - 7 = 3
-2x - 7 = 3
-2x = 10
x = -5
e
-2x - 7 = -3
-2x = 4
x = -2
Portanto x = -5 ou x = -2 é solução da equação modular.
ailymecardosoa:
thanksss
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás